Kinetika Fouling Membran Ultrafiltrasi (UF) Pada Pengolahan Air Berwarna: Pengaruh Interval dan Lamanya Pencucian Balik (Backwashing) Membran - Mahmud Mahmud (Universitas Lambung Mangkurat, 2005)
One of the most common problems encountered in water treatment application of membranes is fouling by natural organic matter. Peat water as surface water has large of natural organic matter in various molecular weights, and the big component is small molecular weight. The laboratory-scale ultra filtration (UF) experiments were conducted to determine the effect interval and duration of backwashing membrane to happened fouling membrane for removing organic matter and colour of peat water. The ultra filtration membranes used in this research are made of plymeric cellulose acetate 13%, dimethylformamide 36% and acetone 51%. Membranes are prepared by applying method of phase inversion. Time interval for backwashing with aquadest is 1 and 5 hours with pre coagulation and 1 hour for peat water without pre-treatment. The process performs similar of flux recovery 91,07% and 90,57%. In addition without pre-treatment, the 1 hour interval backwashing shows low level of recovery flux 55,64%.